OVERVIEW OF PREGNANT WOMAN BEHAVIOUR AGAINST ANTENATAL CARE COMPLIANCE IN KEBON KALAPA VILLAGE, CISARUA SUB-DISTRICT, SUMEDANG REGENCY, WEST JAVA IN 2019 - Udjung, Gorga I. V. W.; Simarmata, Vidi Posdo A. (International Journal of Research -GRANTHAALAYAH, 2021)
Antenatal services, according to standards, are services provided to pregnant women, given four times during pregnancy. According to RISKESDAS Data, the province’s antenatal care proportion in Indonesia was 2013 at 95.2% and 2018 at 96.1% over the past five years. This study was designed to describe pregnant women against antenatal mediation in Kebon Kalapa Village, Cisarua District, Sumedang, West Java, 2019. This research is a descriptive-analytic study. Sampling using purposive sampling technique and obtained a total sample of 22 respondents. The results showed significant differences between pregnant women’s knowledge, attitudes, and practices about the regulation of antenatal care in Kebon Kalapa Village, Cisarua District, Sumedang, West Java, in 2019. The research studies showed that there was a significant difference between knowledge, attitudes and antenatal care practices in Kebon Kalapa Village, Cisarua District, Sumedang, West Java, 2019 with an overview of good knowledge is nine people (40.9%) and sufficient knowledge of 4 people (18.2%). An overview of a good attitude is 21 people (95.5%), and an overview of good practice is 17 people (77.3%). The overview of antenatal care is 18 people (81.8%). Most pregnant women in Kebon Kalapa Village, Cisarua District, Sumedang Regency, West Java In 2019 have good knowledge, and most pregnant women in Kebon Kalapa Village, Cisarua District, Sumedang District, West Java, 2019 have a positive attitude. Most pregnant women in Kebon Kalapa Village Cisarua Sumedang Regency, West Java 2019 have positive practice, and most pregnant women in Kebon Kalapa Village, Cisarua Sub-District, Sumedang District, West Java, 2019 are obedient to antenatal care.